2001
DOI: 10.1097/00005344-200107000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Increases Endothelin-1 Synthesis in Human Coronary Artery Smooth Muscle Cells

Abstract: Endothelins, nitric oxide, and oxygen-derived free radicals decisively regulate vascular tone. An imbalance in the biosynthesis of these substances in pathophysiologic conditions may trigger vasospasm and promote the development of atherosclerosis. Previous studies have shown that oxygen-derived free radicals can increase the synthesis of endothelin-1 in cultured endothelial cells. Interestingly, conditions of increased oxidative stress within smooth muscle cells as induced by angiotensin II infusion or hyperc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
1
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(98 citation statements)
references
References 22 publications
8
82
1
7
Order By: Relevance
“…The production of endothelin is stimulated by both angiotensin II and oxidative stress in endothelial and smooth muscle cells. [57][58][59] An increased endothelin-1-like and big endothelin-1-like immunoreactivity in the tunica media of tolerant vessels has been demonstrated during nitrate treatment in two different animal models. 60,61 In one report, exposure of normal vessels to low concentrations of endothelin-1 caused a hypersensitivity to vasoconstricting agents similar to that observed in nitrate tolerant vessels.…”
Section: Neurohormonal Activation and The Control Of ·O 2 ؊ Productionmentioning
confidence: 99%
“…The production of endothelin is stimulated by both angiotensin II and oxidative stress in endothelial and smooth muscle cells. [57][58][59] An increased endothelin-1-like and big endothelin-1-like immunoreactivity in the tunica media of tolerant vessels has been demonstrated during nitrate treatment in two different animal models. 60,61 In one report, exposure of normal vessels to low concentrations of endothelin-1 caused a hypersensitivity to vasoconstricting agents similar to that observed in nitrate tolerant vessels.…”
Section: Neurohormonal Activation and The Control Of ·O 2 ؊ Productionmentioning
confidence: 99%
“…36 Just as endothelin can cause oxidative stress, endothelin also increases in response to oxidative stress. 50 Therefore, endothelin could be increased in postmenopausal women because of reductions in estradiol and increases in Ang II, oxidative stress, or androgens.…”
Section: Does Endothelin Play a Role In Postmenopausal Hypertension?mentioning
confidence: 99%
“…40,41 Whereas ET-1 can increase oxidative stress, there are a number of reports that reactive oxygen species can increase ET-1 production in cultured endothelial cells and vascular smooth muscle cells. [42][43][44][45] Hydrogen peroxide and superoxide can increase ET-1 synthesis, and 8-iso prostaglandin F2ϰ, a product formed by free radical catalyzed lipid peroxidation, also can have similar effects. 42 The relevance of these observations is unclear given that Saito et al observed contrasting findings that hydrogen peroxide actually decreases ET-1 mRNA and protein synthesis in endothelial cells.…”
Section: Et-1 and Oxidative Stressmentioning
confidence: 99%